Analisis Tahap Berpikir Mahasiswa STAIN Purwokerto pada Materi Geometri - Maria Ulpah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract : Geometry is one of the most important topics in mathematic. A teacher may know students’ geometric thought so the students can learan effectively. This paper describes how student learn to reason in geometry referring to Van Hiele theory. The best know part of the theory are the five levels which the van Hieles postulated. The levels are visualization, analysis, abstraction, deduction and rigor. The study shows that the student are in alanysis level generally. Keyword: Geometry, Van Hiele Teory, Intellectuality, Student.